2024
DOI: 10.3389/fcimb.2024.1358873
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell activation triggered by SARS-CoV-2 causes inflammation in brain microvascular endothelial cells and microglia

Meng-Li Wu,
Chengzuo Xie,
Xin Li
et al.

Abstract: SARS-CoV-2–induced excessive inflammation in brain leads to damage of blood–brain barrier, hypoxic-ischemic injury, and neuron degeneration. The production of inflammatory cytokines by brain microvascular endothelial cells and microglia is reported to be critically associated with the brain pathology of COVID-19 patients. However, the cellular mechanisms for SARS-CoV-2–inducing activation of brain cells and the subsequent neuroinflammation remain to be fully delineated. Our research, along with others’, has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It suggested that these aging-related genes could play an important role in activated mast cell-mediated damage to blood–brain barrier, providing novel therapeutic targets for ICH. Mast cell-mediated endothelial injury is prevalent in the central nervous system, 70 respiratory system, 71 cardiovascular system, 72 and intestinal system. 73 Previous research has demonstrated that mast cells can trigger inflammatory responses in human cerebral microvascular endothelial cells through degranulation, leading to disruption of the blood–brain barrier (BBB) during neurological inflammation caused by ICH.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that these aging-related genes could play an important role in activated mast cell-mediated damage to blood–brain barrier, providing novel therapeutic targets for ICH. Mast cell-mediated endothelial injury is prevalent in the central nervous system, 70 respiratory system, 71 cardiovascular system, 72 and intestinal system. 73 Previous research has demonstrated that mast cells can trigger inflammatory responses in human cerebral microvascular endothelial cells through degranulation, leading to disruption of the blood–brain barrier (BBB) during neurological inflammation caused by ICH.…”
Section: Discussionmentioning
confidence: 99%